A quiet life - Walter, Natasha (Harpercollins Publishers, 2016)
Wife. Mother. Spy. Eighteen-year-old Laura Leverett arrives from America for a new life in England. At the side-lines of her cousin's glamorous gatherings, Laura hungers for someone with whom she can discuss the new political ideas sweeping through London. Edward Last is the kindred spirit Laura has been waiting for. But the secret he is carrying will test Laura's ideals to their limits and take them across oceans before tearing them apart